Uterine conserving surgery in a case of cervicovaginal agenesis with unicornuate uterus - Vineet Mishra; Suwa Ram Saini; Sakshi Nanda; Sumesh Choudhary; Priyankur Roy; Tanvir Singh (Wolters Kluwer Medknow Publications, 2016)
The presence of cervicovaginal agenesis with unicornuate uterus is a very rare mullerian anomaly. Its true incidence is still unknown. The presence of functioning unicornuate uterus poses a great challenge for a gynecologist because a successful repair could restore normal menses and may preserve a patient's fertility. Hence, we report a case of 16-year-old unmarried female who presented with chief complaints of primary amenorrhea with cyclical lower abdominal pain. On clinical and radiological evaluation, she was diagnosed with complete cervicovaginal agenesis with right unicornuate uterus (hematometra and hematosalpinx). She underwent vaginoplasty (McIndoes method) along with uterovaginal anastomosis by neocervix formation, in order to preserve her uterus. On follow-up, her vagina was completely healed, and she was menstruating normally.